Weather acceleration durability of biopolymer membranes PVA modified with cassava starch used in the treatment of wounds - Hao, Nguyen Huong; Trinh, Pham The; Tung, Nguyen Huy; Tien, Mai Van; Thanh Nhan, Nguyen Thi (Vietnam Journal of Chemistry, 2016)
This research shows the results of accelerated weather durability of biopolymer membranes polyvinyl alcohol (PVA) modified with cassava starch (TBS) in biomedical uses, in order to evaluate the stability of biopolymer membranes PVA/TBS in the storage conditions. For the purpose of determining the using time of PVA/TBS membranes in the applications of covering, moisturizing, reducing pain in burn wound treatment. The characteristic properties of PVA/TBS biopolymer membranes and PVA membranes before and after accelerated weather testing were examined, such as: mechanical strength (tensile strength, elongation at break), infrared spectrum (IR) and the scanning electron microscope images (SEM). The results showed PVA/TBS biopolymer membranes aging resistant, against UV rays were better than ordinary PVA membranes. The using time of PVA/TBS membrane has been identified as 36 months. Keywords. Biopolymer, polyvinylalcohol, cassava starch, weather acceleration.